2008
DOI: 10.1016/j.cej.2007.07.083
|View full text |Cite
|
Sign up to set email alerts
|

3D-glass–ceramic scaffolds with antibacterial properties for bone grafting

Abstract: A 3D-scaffold for bone tissue engineering should show an interconnected macroporous network with pores exceeding 100 µm to favor cell penetration and vascularisation, should be osteoproductive and should exhibit sufficient mechanical strength. In this work, bioactive glass ceramic scaffold characterised by a network of pores and struts were obtained using the sponge impregnation method. Specifically, 3D-scaffolds with a total porosity of 75 vol.% and 2MPa of compressive strength were prepared through a fine tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 31 publications
1
84
0
2
Order By: Relevance
“…Recent developments related to bone TE try to bridge this gap and overcome this problem by architectures and components carefully designed from comprehensive levels, i.e., from the macro-, meso-, micrometer down to the nanometer scale [101], including both multifunctional bioactive glass composite structures (see §3.2) and advanced bioactive glass-ceramic scaffolds exhibiting oriented microstructures, controlled porosity and directional mechanical properties [99,[102][103][104][105], as discussed in the following paragraphs. Most studies have investigated mainly the mechanical properties, in vitro and cell biological behavior of glass-ceramic scaffolds [13][14][15]30,43,52,94,95,97,99,, as summarized in Table 1, and scaffolds with compressive strength [99,102] and elastic modulus values [99,105] in magnitudes far above that of cancellous bone and close to the lower limit of cortical bone have been realized. Fu et al [99] fabricated bioactive glass (13-93) scaffolds with oriented (i.e., columnar and lamellar) microstructures and found that at an equivalent porosity of 55-60%, the columnar scaffolds had a compressive strength of 25 ± 3 MPa, compressive modulus of 1.2 GPa, and pore width of 90-110 µm, compared to values of 10 ± 2 MPa, 0.4 GPa, and 20-30 μm, respectively, for the lamellar scaffolds.…”
Section: Bioactive Glass Based Glass-ceramic Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments related to bone TE try to bridge this gap and overcome this problem by architectures and components carefully designed from comprehensive levels, i.e., from the macro-, meso-, micrometer down to the nanometer scale [101], including both multifunctional bioactive glass composite structures (see §3.2) and advanced bioactive glass-ceramic scaffolds exhibiting oriented microstructures, controlled porosity and directional mechanical properties [99,[102][103][104][105], as discussed in the following paragraphs. Most studies have investigated mainly the mechanical properties, in vitro and cell biological behavior of glass-ceramic scaffolds [13][14][15]30,43,52,94,95,97,99,, as summarized in Table 1, and scaffolds with compressive strength [99,102] and elastic modulus values [99,105] in magnitudes far above that of cancellous bone and close to the lower limit of cortical bone have been realized. Fu et al [99] fabricated bioactive glass (13-93) scaffolds with oriented (i.e., columnar and lamellar) microstructures and found that at an equivalent porosity of 55-60%, the columnar scaffolds had a compressive strength of 25 ± 3 MPa, compressive modulus of 1.2 GPa, and pore width of 90-110 µm, compared to values of 10 ± 2 MPa, 0.4 GPa, and 20-30 μm, respectively, for the lamellar scaffolds.…”
Section: Bioactive Glass Based Glass-ceramic Scaffoldsmentioning
confidence: 99%
“…The high amounts of Na 2 O and CaO, as well as the relatively high CaO/P 2 O 5 ratio make the glass surface highly reactive in physiological environments [11]. Other bioactive glass compositions developed over the years contain no sodium or have additional elements incorporated in the silicate network such as fluorine [13], magnesium [14,15], strontium [16][17][18], iron [19], silver [20][21][22][23], boron [24][25][26][27], potassium [28] or zinc [29,30]. Fabrication techniques for bioactive glasses include both traditional melting methods and sol-gel techniques [1, 3,4,10,[31][32][33], the latter are being highlighted elsewhere [34] and are not covered in this review.…”
Section: Introductionmentioning
confidence: 99%
“…6. The microstructure of the glass as well as its porosity of 82% are crucial textural parameters for enhanced cell adhesion, vascularisation, infiltration, and osteointegration on the glass material [26][27][28][29][30][31].…”
Section: Microstructurementioning
confidence: 99%
“…In summary, the properties of ceramic with Ag contained nanomaterial addition greatly depended on the microstructure and chemical states of Ag and nanomaterials, no matter the loading position of framework or surface. The properties of some nanomaterial loaded ceramics are listed in Table 1 [8,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%